Analisis Pendapatan Usahatani Cabai Merah (Capsicum Annum L.) (Studi Kasus Petani Cabai Merah di Desa Sawaru, Kecamatan Camba, Kabupaten Maros, Provinsi Sulawesi Selatan) - Dwi Arti; Ni Made Viantika S; Eymal B. Demmallino (Manajemen Agribisnis: Jurnal Agribisnis, 2023)
The development of chili farming businesses needs to be carried out related to needs of chili consumption in line with increasing population. The purpose of the study was determine the amount of costs used by farmers in carrying out red chili farming and analyze the income level of red chili farmers in Sawaru Village. This research was carried out in Sawaru Village, Camba District, Maros Regency with the data used in the form of primary data and secondary data. The research instrument used in this study in the form of structured questionnaire, which is used to obtain the required data. Sampling was carried out by simple random sampling, namely farmers who carried out red chili farming with the number of respondents taken as many as 37 farmers. Data collection techniques include documentation and structured interviews on number of respodents. The data analysis process in this study was carried out quantitatively. Quantitative analysis is carried out by tabulating analysis so that the data can be simplified and easy to read. The results showed that theaverage acceptance of red chili farming was Rp.17,228,378 and the average production cost is Rp.4,886,770 then the average income received by farmers is Rp.12,341,608 per growing season.